Bien-être subjectif d'élèves de CM2 : les relations au cœur des « moments spéciaux » - Sophie Necker; Joséphine Rémon; Émilie Magnat
With the aim of studying the importance of relationships in schoolchildren's well-being, we explore a methodological set-up called the "special moment box". This data collection tool, in the shape of notes anonymously written by the pupils, offers us a double access to the subjective well-being of fifth grade pupils, via the mention of others and relationships, and via the related emotions. We analyse our corpus through the mention of others in their diversity, involved in relationships as schoolmates, friends, towards the construction of the collective, in privileged relationships with the referring adults, around pedagogical scenarios highlighting performance, self-exposure, creation or humour. Different degrees of awareness of the added value of the relationship appear in the notes, which express in turn the benefits for the well-being of the individual pupil and/or for that of the class group.